Correlation between Maternal Infection and Infant Cholestasis - Liofelita Christi Adhi Mulia; I Gusti Made Reza Gunadi Ranuh; Ernawati Ernawati (JUXTA: Jurnal Ilmiah Mahasiswa Kedokteran Universitas Airlangga, 2021)
Introduction: Infant cholestasis has been associated to viral infection. Cytomegalovirus in the pathogenesis of neonatal hepatitis has been already known and it is one of the possible etiological of biliary atresia. The aim of this study was to outline the correlation between maternal infection and infant cholestasis (aged 0-1 year old) in Department of Pediatrics Dr. Soetomo General Hospital, Surabaya. Methods: A case-control study of pregnant women who gave birth in Dr. Soetomo General Hospital from June 2016 to June 2017. The data were taken from medical records. The cases were defined as pregnant women with babies who had cholestasis, and the control was pregnant women who gave birth to a baby without cholestasis within the age of 0-1 year old. Sample cases in this study were drawn from the total population, with the inclusion criteria babies who had cholestasis, and exclusion criteria that include complications of pregnancy and a history of infant’s parent with genetic disorders. The control variable studied was maternal infection history and sex. Samples were taken by purposive control. The data were obtained then summarized and analyzed by univariate and bivariate, using the chi-square table analysis. Results: The number of cases that met the inclusion criteria were 68 patients, and the amount of control taken was 110 patients. The total number of patients studied was 178 patients. Univariate analysis found the cholestasis was more common in mother with infection during pregnancy (73.53% from the total of  cholestasis). Bivariate analyzes found relationship between pregnancy infection and cholestasis (p = <0.001, or = 20.726). Conclusion:The maternal infection is significantly associated with cholestasis in infants.